Retention of quiet eye in older skilled basketball players - Fischer, L.; Rienhoff, R.; Tirp, J.; Baker, J.; Strauss, B.; Schorer, J. (Journal of Motor Behavior, 2015)
There is mounting research to suggest that cognitive and motor expertise is more resistant to age-related decline than more general capacities. The authors investigated the retention of skills in medium-aged skilled (n = 14) and older-aged skilled (n = 7) athletes by comparing them with medium-aged less skilled (n = 15) and older-aged less skilled (n = 15) participants. Participants performed basketball free throws and dart throws as a transfer task under standardized conditions. Motor performance (accuracy) and perceptual performance (quiet eye) were examined across the four groups. There were significant differences between skill groups and age groups in throwing accuracy on both throwing tasks. Skilled players outperformed less skilled and medium-aged players outperformed older-aged players in basketball and dart throws. There were no significant differences in quiet eye duration across the skill or age groups in either task. These results indicate expertise in a perceptual motor task such as the basketball free throw can be retained in older athletes and that present models of skill maintenance should be re-evaluated to consider the issue of transfer.